Optimal timing of fluorine-18-fluoromisonidazole positron emission tomography/computed tomography for assessment of tumor hypoxia in patients with head and neck squamous cell carcinoma. Issue 9 (September 2018) - Chatterjee, Abhishek; Gupta, Tejpal; Rangarajan, Venkatesh; Purandare, Nilendu; Kunder, Shreya; Murthy, Vedang; Budrukkar, Ashwini; Ghosh-Laskar, Sarbani; Agarwal, JaiPrakash
Abstract : Objectives: The aim of this study was to identify the optimal timing of fluorine-18-fluoromisonidazole ( 18 F-MISO) PET/CT imaging to assess hypoxia in patients with head and neck squamous cell carcinoma. Patients and methods: Eighteen patients underwent pretreatment 18 F-MISO PET/CT imaging after providing written informed consent. PET scans were acquired at 1, 3, and 5 h after injection of the radionuclide. The mean standardized uptake value (SUV) within a spherical region of interest placed on the contralateral neck musculature at the level of the largest tumor dimension was labeled as background. A value 1.5 times the background was deemed the threshold for significant hypoxia. Using this threshold, volumetric regions of interest encompassing the tumor were placed and hypoxic tumor volume (HTV) was generated for the primary tumor. Repeated-measures analysis of variance was used to compare the 18 F-MISO PET/CT metrics across the three time-points. The volume of the primary tumor was also correlated with HTV. Results: The mean SUV of the background decreased consistently over time, resulting in increased focality of 18 F-MISO uptake in the tumor tissues. Analysis of variance showed statistically significant differences in the mean SUV measurements of the background between the 1-h and the 3-h time-points ( P =0.034) as well as the 1-h and the 5-h time-points ( P =0.034). In parallel, the mean HTV increased from 1.72 cm 3 at 1 h after injection to 6.52 cm 3 at 3 h and further to 7.24 cm 3 at 5 h, with a statistically significant difference between the 1-h and the 3-h scans ( P =0.023) and the 1-h and the 5-h scans ( P =0.023). There was a moderately good positive correlation between gross tumor volume on planning computed tompography (CT) and HTV at 3 h on the 18 F-MISO scan (Pearson's correlation co-efficient ' r '=+0.753; P <0.0001). Conclusion: The contrast resolution of 18 F-MISO PET/CT scans in head and neck squamous cell carcinoma is suboptimal with early image acquisition, but improves significantly after delayed imaging. Increasing volume of tumor at the primary site is associated with an increase in hypoxia.